The root-knot nematodes of banana: Meloidogyne incognita (Kofoid & White, 1919) Chitwood, 1949 (and) Meloidogyne javanica (Treub, 1885) Chitwood, 1949 - Waele, D. de; Davide, R.G.; International Network for the Improvement of Banana and Plantain (1999)
THE ROOT-KNOT NEMATODES OF BANANA (Meloidogyne incognita -Kofoid & White, 1919- Chitwood, 1949; Meloidogyne javanica -Treub, 1885 - Chitwood, 1949). The root-knot nematodes Meloidogyne incognita and Meloidogyne javanica occur on banana and plantain roots wherever this crop is grown. Meloidogyne arenaria and occasionally some other Meloidogyne species may also be found associated with banana and plantain. In spite of their widespread occurrence and high abundance, root-knot nematodes are not considered important pathogens of banana and plantain. Root-knot nematodes often occur on banana roots together with the other pathogenic nematode species Radopholus similis and Pratylenchus spp. The damage caused by these other nematode species is more visible (root necrosis) and more destructive (toppling of plants).